Comparison of L‐strut preservation in endonasal and endoscopic septoplasty: a cadaveric study. Issue 2 (4th November 2013) - Russell, Marika D.; Kangelaris, Gerald T.
<x xml:space="preserve">Abstract</x> Background Preservation of an adequate cartilaginous L‐strut to prevent complications of septoplasty has been long recognized as critical. However, no previous study has examined the dimensions of the L‐strut that remain after septoplasty. We hypothesized that differences in exposure and visualization between endoscopic and endonasal techniques would result in differences in preserved L‐strut dimensions. We designed this study to determine L‐strut dimensions after performance of septoplasty with endonasal and endoscopic technique. Methods We performed a cadaveric study with 24 heads randomly assigned to undergo endonasal vs endoscopic septoplasty by senior resident surgeons (postgraduate year 4 [PGY‐4] and PGY‐5). Removal of the skin–soft tissue envelope and mucoperichondrium was performed after septoplasty to permit direct measurement of the L‐strut. Minimum and maximum widths were recorded for the caudal and dorsal segments; a single measurement was recorded for the width at the anterior septal angle. Statistical analysis was carried out using the 2‐tailed distribution Student t test. Results There was no significant difference in caudal or anterior septal width between endonasal and endoscopic techniques. There was a statistically significant difference in dorsal segment width for both minimum and maximum values, with endoscopic technique resulting in a narrower dorsal segment than endonasal technique (mean minimum value of 10.8 mm vs 13.2 mm, respectively, p = 0.03; and mean maximum value of 12.6 mm vs 16 mm, respectively, p = 0.01). There was significant variation in resident surgeon performance, with the performance of 1 resident surgeon accounting for the difference in minimum dorsal width. Conclusion Differences in exposure and visualization between endoscopic and endonasal septoplasty techniques may result in differences in preserved L‐strut dimensions. Care should be taken with endoscopic technique to prevent overly aggressive resection of septal cartilage, particularly with learners of this technique.